ETIOLOGY AND THERAPEUTIC MANAGEMENT OF LOWER RESPIRATORY TRACT INFECTIONS: A CURRENT REVIEW - Cholewiński, Kacper; Karolak, Dominika; Białowąs, Tymoteusz; Kuśmierowska, Natalia; Valipur Kolti, Daria; Kuś, Monika; Słomkowski, Grzegorz; Polak, Milena; Nowak, Magdalena; Wiśniewski, Konrad (International Journal of Innovative Technologies in Social Science, 2026)
Lower respiratory tract infections remain a primary global cause of morbidity and mortality, particularly devastating for children under five and adults over seventy. This study focuses on analyzing the diverse etiology of these infections – including viral, bacterial, and atypical pathogens – to establish therapeutic algorithms that ensure effective treatment while curbing the critical issue of antimicrobial overuse. Based on an extensive review of current literature and epidemiological data, the research highlights community-acquired, hospital-acquired, and ventilator-associated pneumonia. Findings from 2023 indicate that general mortality rates have returned to pre-pandemic levels, though mortality remains highest when pneumonia precedes mechanical ventilation. While Streptococcus pneumoniae is the leading bacterial cause of death globally, Staphylococcus aureus and Pseudomonas aeruginosa dominate hospital settings. Among young children, Respiratory Syncytial Virus (RSV) is the primary pathogen. Management strategies identify amoxicillin as the first-line treatment for community-acquired cases, whereas hospital-acquired infections require empirical coverage for MRSA and Gram-negative bacteria. Prevention is bolstered by vaccinations and monoclonal antibodies like Nirsevimab for RSV. Ultimately, because lower respiratory tract infections etiology is highly dependent on age and comorbidities, rapid differential diagnosis is essential to combat antibiotic resistance. Effective prevention through immunization and patient education remains the most successful strategy for reducing hospitalizations related to severe respiratory infections.